PENGELOLAAN EKOSISTEM MANGROVE BERKELANJUTAN BERBASIS SES DI DESA UPA KECAMATAN TOBELO TENGAH - Lawene, Maria N; Tetelepta, Johannes M S; Pello, Frederika S (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2025)
Mangrove ecosystems have ecologically important values for the community and make a major contribution to support the sustainability of life. This study aims to analyze the ecological habitat of mangrove ecosystems, analyze mangrove ecosystem management with an ecological approach, determine sustainable management strategies for mangrove ecosystems in Upa Village. The research was conducted from January to May 2024 in Upa Village, Central Tobelo District. Data were collected through observation and interviews. Mangrove data were collected using belt transect, while socio-economic data were collected using questionnaires to 90 respondents. Data mangrove processed with Microsoft Excel, analysis of problems and connectivity of social ecological systems using DPSIR analysis followed by AHP. Water quality values obtained are still in accordance with quality standards to support mangrove growth. Four types of mangrove species were found on the coast of Upa Village with a density level including the good category. The INP value for the tree and sapling category is dominated by Sonneratia alba, while for the sapling category is dominated by Rhizophora apiculata. There are 3 strategies for sustainable mangrove ecosystem management in Upa Village, namely environmental education (0.516), strengthening regulations (0.252), and fishermen infrastructure (0.232) with priority strategies focused on environmental education. ABSTRAK Ekosistem mangrove memiliki nilai penting secara ekologis bagi masyarakat serta memberikan kontribusi yang besar untuk menunjang keberlangsungan kehidupan. Penelitian ini bertujuan untuk menganalisis habitat ekologi ekosistem mangrove, menganalisis pengelolaan ekosistem mangrove dengan pendekatan ekologi, menentukan strategi pengelolaan berkelanjutan ekosistem mangrove di Desa Upa. Penelitian dilakukan pada Januari-Mei 2024 di Desa Upa Kecamatan Tobelo Tengah. Pengambilan data dilakukan melalui observasi dan wawancara. Pengambilan data mangrove menggunakan belt transect, sedangkan data sosial ekonomi menggunakan kuesioner terhadap 90 responden. Data mangrove diolah dengan microsoft excel, analisis permasalahan dan konektivitas sistem sosial ekologi menggunakan analisis DPSIR yang dilanjutkan dengan AHP. Nilai kualitas air yang diperoleh masih sesuai baku mutu untuk mendukung pertumbuhan mangrove. Ditemukan 4 jenis spesies mangrove di pesisir Desa Upa dengan tingkat kerapatan termasuk kategori baik. Nilai INP untuk kategori pohon dan anakan didominasi oleh Sonneratia alba, sedangkan untuk kategori sapihan didominasi oleh Rhizophora apiculate. Diperoleh 3 strategi untuk pengelolaan ekosistem mangrove berkelanjutan di Desa Upa yaitu yaitu pendidikan lingkungan (0.516), pengautan regulasi (0.252), dan sarana prasarana nelayan (0.232) dengan strategi prioritas difokuskan pada pendidikan lingkungan. Kata Kunci: Mangrove, DPSIR, AHP, keberlanjutan, Desa Upa